Philosophical Analysis of Multi-Contract Terminology Perspective of Sharia Economic Law - Muhammad Yunus; Sofyan Al Hakim; Iwan Setiawan (al-Afkar, Journal For Islamic Studies, 2023)
This research aims to examine philosophically the existence of al-'Uqûd al-Murakkabah (multiple contracts). The search is concentrated on the opinions of fuqaha and muhadisin, as well as its application in Islamic Financial Institutions. This study is urgent, because in the form of a single contract is not able to respond to contemporary financial transactions that are always moving and affected by the financial industry both nationally, regionally and internationally. By using qualitative methods and literature, this study concludes that, first, the contemporary fiqh muamalah view of the hadiths related to the hybrid contract model leads to the wording of the prohibition of bai'ataini fi bai'atin (two trades in one trade), Second, the construction of the hybrid contract model in Islamic banks is aimed at the construction of al-'Uqûd al-Mutaqâbilah (dependent or conditional contract), which is implemented in the Bank Guarantee (BG), and al-'Uqûd al-Mujtami'ah